International critical tables of numerical data, physics, chemistry and technology - Washburn, Edward W. 1881-1934; West, Clarence J. 1886-1953; Dorsey, N. Ernest 1873-1959 (Published for the National Research Council by the McGraw-Hill Book Co., 1926)
Offers data on physical, thermodynamic, mechanical, and other key properties and is a major reference source used by those in chemistry, physics, and engineering. Many tables have been "knovelized" to be interactive. The full text of the original print version is available in PDF format (full-text searchable), including original index. All entries in index hyperlinked to their page numbers
Chiefly tables.
Keywords: Numerical calculations -- Tables.; Physics -- Tables.; Chemistry -- Tables.; Technology -- Tables.; Science -- Tables.; Science.; Chemistry.; Physics.; Technology.; elektronické knihy; electronic books